Coexistence, co-responsibility and interdependence as categories important to social pedagogy directed towards building local communities - Naumiuk, Agnieszka (Kultura-Społeczeństwo-Edukacja, 2020)
The article analyzes three categories: co-existence, co-responsibility and interdependence in the context of contemporary discussions about the role of social pedagogy in building local communities. New possible approaches arise while using these concepts for addressing contemporary conditions of the communities which result in new tasks of education. There are analysed also the consequences of the transformation from the previous rather static (territorial) view of local communities, that had the aim to root people in existing social structures, towards more dynamic, open and diverse spaces. They are not considered only as physical places anymore but as new local relations that are being developed, based on not stable, however increasingly popular forms of sharing experiences. For these changes the studied concepts match the new realities and in consequence demand pedagogical considerations.